“Homo Europaeus"? A comparative analysis of advertising (ENTHYMEMA, 2018)
The narrative repertoire of advertising is the only place where producer and consumer, sender and receiver negotiate a common identity format. The analysis of advertising in European countries shows that there is no such thing as the homo europaeus, but that there are two major continental blocks: the Nort-European one, with its monochronic advertisements, narrative formats based on relationships and soft-sell brand representation mechanisms, in which the context is more relevant than the product itself; in Southern Europe, on the other hand, we found polychronic advertising, narrative formats based on the idea of performance and mechanisms of representation of individual hard-sell products, in which the context loses its prominence.
Keywords: Advertising; storytelling; hard-sell / soft-sell; monochronic / polichronic societies; nationalism; life-narrative account